Faktor Pemilihan Metode Kontrasepsi IUD di Puskesmas Singkut Kabupaten Sarolangun - Hasrita Octaliana; Nurul Fatimah Susanti; Endah Purda Listya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Family Planning Program is a government initiative designed to balance population growth with existing resources and needs. This study aims to identify the factors associated with the choice of IUD contraception at the Singkut Health Center in Sarolangun Regency, Jambi Province. The research employed an analytical design with a cross-sectional approach. The study population consisted of 3,985 active family planning acceptors in 2023, from which 351 respondents were selected using random sampling techniques. Data were collected through questionnaires and analyzed univariately to assess levels of knowledge, attitudes, partner support, socio-cultural influences, and IUD contraceptive choices. Bivariate analysis was conducted using the chi-square test. The statistical results indicated that the majority of respondents (69.2%) had good knowledge about IUDs, most (80.1%) had positive attitudes, a significant portion (61.8%) received partner support, and the majority (60.1%) lived in supportive socio-cultural environments. However, most respondents (82.1%) did not choose to use IUD contraception. The chi-square test showed that knowledge (p = 0.000), attitude (p = 0.003), and partner support (p = 0.000) were significantly related to IUD use, whereas socio-cultural factors (p = 0.804) were not. The study concludes that knowledge, attitudes, and partner support are significantly associated with the decision to use IUD contraception at Singkut Health Center in 2024. Therefore, it is recommended that healthcare providers strengthen health promotion efforts regarding IUDs, especially through direct communication with the community by involving husbands and other family members.